Využití doménových znalostí při aplikacích GUHA procedur - Ralbovský, Martin (2006)
We presume for this work, that the GUHA procedures' abilities can be extended by using domain knowledge in a suitable form. There are two types of domain knowledge used in this work: background knowledge and ontologies. Background knowledge is a relatively unknown, yet perspective type of domain knowledge containing rules from domain experts in a written form. The work describes this knowledge and introduces suitable rule formalization. Furthermore, a tool for rule validation is described and implemented. The implementation is done in the Ferda environment, a modular environment for visual GUHA data mining. The work also describes first practical experience with this tool. Concerning domain ontologies, the work greatly extends up-to-date knowledge of usage of ontologies in the GUHA data mining. There are all the former techniques for ontology usage mentioned and extended; in suitable cases the implementation design in Ferda environment is presented. The results of the work are discussed with respect to further usage in the Ever-Miner system, a next generation knowledge discovery tool